Redesigning the Employer Value Proposition in Times of Crisis - Katarzyna Łazorko (European Management Studies)
Purpose: The purpose of the paper was to explore how the largest companies in Poland responded to the changing socio-political situation (the COVID-19 pandemic, the war in Ukraine, the inflation) in their employer branding communication, with potential candidates for jobs, especially in the aspect of their Employer Value Proposition (EVP) building. Methodology: The research examined whether the 50 biggest Polish enterprises changed their external employer branding communication via their web pages between 2019 and 2023. In the study, the online content analysis technique was used to review “Career” and relevant web pages. Findings: The presentation of changing expectations of candidates, as well as analysis of the content of the entrepreneurs’ web pages lead to the conclusion that not many Polish enterprises have changed their Employer Value Proposition (EVP) in the last four years to adjust to expectations of potential employees (about 30% in the sample), although, due to their scale of operation their marketing budgets are probably higher than in the case of the rest of the market. There may be many reasons behind that situation, including the specificity of different industries, as well as unpredictability, and suddenness of changes in their environment. The expectations of employees have changed significantly in the last four years, due to COVID-19 and some political and economic occurrences, and the process has not finished yet. Consequently, the situation in the labor market is dynamic, although, as observed, some companies react expeditiously to meet the expectations of potential employees. Research limitations: In the case of the study, the employer branding communication channels analysis was limited only to web pages and communication with external audiences, although, web pages and the “Career” bookmarks are indicated by Polish employers as one of the most frequently used tools to communicate with candidates. Another problem can be identified when any overall assumptions are made in the area of employer branding. The companies chosen for the study operate in different sectors and the specification of their performance and situation in the labor markets they target is different. Originality/value: The paper contributes to the discussion on employer branding in Poland. The topic is extensive and provides many opportunities for analyses conducted from various perspectives.